Myeloid-Derived Suppressor Cells as Key Players and Promising Therapy Targets in Prostate Cancer - Siemińska, Izabela; Baran, Jarek (Frontiers in Oncology, 2022)
Prostate cancer (PC) is the second most often diagnosed malignancy in men and one of the major causes of cancer death worldwide. Despite genetic predispositions, a crucial role in PC development plays environmental factors, including a high-fat diet, obesity, sedentary lifestyle, infections of the prostate, and exposure to chemicals or ionizing radiation. Moreover, due to a lack of, or insufficient T cell infiltration and its immunosuppressive microenvironment, PC is frequently classified as a "cold" tumor. This is related to the absence of tumor-associated antigens, lack of T cell activation and their homing into the tumor bed, and the presence of immunological cells with regulatory functions, including myeloid-derived suppressor cells (MDSCs), regulatory T cells (Treg), and tumor-associated macrophages (TAMs). All of them by a variety of means hamper anti-tumor immune response in the tumor microenvironment (TME), stimulating tumor growth and formation of metastases. Therefore, they are emerging as potential anti-cancer therapy targets. This article is focused on MDSCs concerning their function and role in the initiation and progression of PC. Clinical trials directly targeting this cell population or affecting its biological functions, thus limiting its pro-tumorigenic activity, are also presented.